Analisis Value Engineering Pekerjaan Atap Rumah Sakit Rodliyah Achid Moga Pemalang - Hanida Isna Reza Pahlevi; Kartono Wibowo; Rachmat Mudiyono (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Roofing work plays an important role in hospital building construction because it affects costs, time, comfort, and structural performance. In the Muhammadiyah Rodliyah Achid Moga Pemalang Hospital Building Construction Project, the existing Kliplok zincalume roofing system was costly and had low productivity. This study aims to obtain more efficient roof design alternatives through Value Engineering (VE) based on SAVE International standards, including information gathering, FAST function analysis, creative stage, evaluation, and development. Two alternatives were developed: Alternative 1 uses SDS tapping screws with 3.0 mm CNP purlins, and Alternative 2 uses 2.3 mm CNP purlins. Both alternatives fulfill the main function with a value index >1.0. Alternative 1 provides the highest cost savings of 27.96%, increases productivity from 25 to 35 m²/person-day, and reduces the implementation duration by four days. A 10-year Life Cycle Cost analysis shows the lowest cost in Alternative 1. Value Engineering has proven to be effective in improving the cost efficiency and performance of hospital roof work.